Caribbean integration law - Berry, David S. (Oxford : Oxford University Press, 2014)
Two key regional organisations in the Caribbean, the Caribbean Community and the Organisation of Eastern Caribbean States, had their roles fundamentally expanded in 2001 by treaties that developed a single market and a regional court. This book sets out the new roles of these organisations and their impact on regional integration in the Caribbean.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 14, 2014).
Keywords: Public law -- Caribbean Area; Caribbean Community; O.E.C.S. (Organization)